Relationship Between Knowlwdge and Motivation of Diabetic Patients in Compliance with Diabetes Melitus Diet at UPTD Puskesmas Aceh - Butarbutar, Maria Haryanti; Siregar, Riani Baiduri; Saputra, Heri; Purwana, Rudi (Journal of World Future Medicine, Health and Nursing, 2024)
Diabetes Mellitus is a state of hyperglycemia which is characterized by chronic insulin absolute conditions which can affect carbohydrate metabolism. In 2015 there were 415 million adults with diabetes. The purpose of this study was to analyze the relationship between knowledge and motivation of diabetic patients in adherence to the diabetes mellitus diet at the Aceh Public Health Center. The population in this study were all diabetes mellitus patients who were controlled at the UPTD Puskesmas DTP Lampahan as many as 40 respondents. The sampling technique used is the total population of 40 respondents. The results showed that based on the chi-square test between knowledge of compliance with diabetes mellitus diet obtained p-value = 0.008, motivation with diabetes mellitus obtained p-value = 0.019, motivation with compliance running a diabetes mellitus diet obtained p-value = 0.020, the role of health workers with diabetes mellitus obtained p-value = 0.027. Conclusion Based on the results of the chi-square test, it can be concluded that there is a significant relationship between knowledge, self-motivation and adherence to dieting in people with diabetes mellitus at the UPTD Puskesmas DTP Lampahan.